B-cell receptor reactivity against Rothia mucilaginosa in nodular lymphocyte-predominant Hodgkin lymphoma - Thurner, Lorenz; Fadle, Natalie; Regitz, Evi; Roth, Sophie; Cetin, Onur; Kos, Igor Age; Hess, Simon Mauro; Bein, Julia; Bohle, Rainer Maria; Vornanen, Martine; Sundström, Christer; De Leval, Laurence; et al. (Haematologica (Roma), 2023)
Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is a Hodgkin lymphoma expressing functional B-cell receptors (BCR). Recently, we described a dual stimulation model of IgD+ lymphocyte-predominant cells by Moraxella catarrhalis antigen RpoC and its superantigen MID/hag, associated with extralong CDR3 and HLA-DRB1*04 or HLADRB1* 07 haplotype. The aim of the present study was to extend the antigen screening to further bacteria and viruses. The fragment antibody-binding (Fab) regions of seven new and 15 previously reported cases were analyzed. The reactivity of non-Moraxella spp.-reactive Fab regions against lysates of Rothia mucilaginosa was observed in 5/22 (22.7%) cases. Galactofuranosyl transferase (Gltf) and 2,3-butanediol dehydrogenase (Bdh) of R. mucilaginosa were identified by comparative silver- and immuno-staining in two-dimensional gels, with subsequent mass spectrometry and validation by western blots and enzyme-linked immunosorbent assay. Both R. mucilaginosa Gltf and Bdh induced BCR pathway activation and proliferation in vitro. Apoptosis was induced by recombinant Gltf/ETA’-immunotoxin conjugates in DEV cells expressing recombinant R. mucilaginosa-reactive BCR. Reactivity against M. catarrhalis RpoC was confirmed in 3/7 newly expressed BCR (total 10/22 reactive to Moraxella spp.), resulting in 15/22 (68.2%) cases with BCR reactivity against defined bacterial antigens. These findings strengthen the hypothesis of bacterial trigger contributing to subsets of NLPHL.